2014
DOI: 10.20429/tag.2014.000101
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow generalizations of Ramsey theory - a dynamic survey

Abstract: In this work, we collect Ramsey-type results concerning rainbow edge colorings of graphs.If you have corrections, updates or new results which fit the scope of this work, please contact Colton Magnant at coltonmagnant@yahoo.com.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 132 publications
(159 reference statements)
0
59
0
Order By: Relevance
“…Chen and Daykin [5] showed that for each integers ℓ t n , , with ≥ ≥ t n t 2, 25 , and ≥ ℓ ≥ n 2, an edge-coloring of the complete bipartite graph K n n , admits a PC ℓ C 2 if no vertex is incident to t edges of the same color. More related results can be found in surveys [8,9].…”
Section: Color Degree Conditionmentioning
confidence: 58%
See 1 more Smart Citation
“…Chen and Daykin [5] showed that for each integers ℓ t n , , with ≥ ≥ t n t 2, 25 , and ≥ ℓ ≥ n 2, an edge-coloring of the complete bipartite graph K n n , admits a PC ℓ C 2 if no vertex is incident to t edges of the same color. More related results can be found in surveys [8,9].…”
Section: Color Degree Conditionmentioning
confidence: 58%
“…Chen and Daykin showed that for each integers tgoodbreakinfix,ngoodbreakinfix, with tgoodbreakinfix≥2goodbreakinfix,0.33emngoodbreakinfix≥25t, and ngoodbreakinfix≥goodbreakinfix≥2, an edge‐coloring of the complete bipartite graph Kn,n admits a PC C2 if no vertex is incident to t edges of the same color. More related results can be found in surveys .…”
Section: Introductionmentioning
confidence: 69%
“…Other related results can be found in [2,4,11,12]. We refer the interested reader to [5] for a survey of Gallai-Ramsey numbers, with a dynamic version available at [6]. We also state the corresponding conjecture for bipartite graphs.…”
Section: Conjecture 2 ([3]mentioning
confidence: 95%
“…We refer to the survey of rainbow generalizations of Ramsey Theory [10,11] for more information on this topic and a complete list of known results involving Gallai-Ramsey numbers. We are now able to state the conjecture of Fox et al…”
Section: Introductionmentioning
confidence: 99%